Atmospheric Air Pollution and Monitoring 2020
DOI: 10.5772/intechopen.86091
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Agricultural Contaminant Concentrations in Ambient Air

Abstract: Monitoring ambient air to assess environmental exposure and risk for volatile agricultural chemicals requires extensive resources and logistical effort. The cost and technical limitations of monitoring can be mitigated using a validated air dispersion model to simulate concentrations of volatile organic chemicals in ambient air. The SOil Fumigant Exposure Assessment (SOFEA) model was developed to explore volatile pesticide exposure and bystander risk. SOFEA assembles sources and source strengths, uses weather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The development and functionality of SOFEA4 is described in detail by Cryer and van Wesenbeeck. 9 Zou et al 10 studied the sensitivity of AERMOD-simulated SO 2 concentrations to variations in dispersion coefficients, meteorological data, and terrain data at 3 locations in Texas, and found that while variations in meteorology had the most significant effect on simulated concentrations, the dispersion coefficients and terrain data had very limited influence. Long 11 examined the sensitivity of AERMOD-simulated concentrations of SO 2 to variations in 8 model input parameters, including albedo, Bowen ratio, surface roughness, cloud cover, solar radiation, and height at which ambient temperature is measured using meteorological data from the San Francisco Bay Area.…”
Section: Introductionmentioning
confidence: 99%
“…The development and functionality of SOFEA4 is described in detail by Cryer and van Wesenbeeck. 9 Zou et al 10 studied the sensitivity of AERMOD-simulated SO 2 concentrations to variations in dispersion coefficients, meteorological data, and terrain data at 3 locations in Texas, and found that while variations in meteorology had the most significant effect on simulated concentrations, the dispersion coefficients and terrain data had very limited influence. Long 11 examined the sensitivity of AERMOD-simulated concentrations of SO 2 to variations in 8 model input parameters, including albedo, Bowen ratio, surface roughness, cloud cover, solar radiation, and height at which ambient temperature is measured using meteorological data from the San Francisco Bay Area.…”
Section: Introductionmentioning
confidence: 99%